Collective Rights and Legal Theory. More ideology than theory - Sauca, José María (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
The theoretical treatment of collective rights and their controversial nature maintain important relevance both from the political and moral philosophical perspective and from that corresponding to legal dogmatics. However, the treatments of this category formulated by legal theory are receiving less and unjustified attention. In this paper, special attention is given to the study of Caracciolo, and Jovanović’s respective works on the subject. It concludes that the intended theoretical approaches of conceptual analysis collapse into an ideological approach on the acceptance or rejection of the category.
Keywords: Theory and ideology; rights; cultural rights